Differentiation of different stages of brain tumor infiltration using optical coherence tomography: Comparison of two systems and histology - Strenge, Paul; Lange, Birgit; Draxinger, Wolfgang; Grill, Christin; Danicke, Veit; Theisen-Kunde, Dirk; Hagel, Christian; Spahr-Hess, Sonja; Bonsanto, Matteo M.; Handels, Heinz; Huber, Robert; Brinkmann, Ralf (Frontiers in Oncology, 2022)
The discrimination of tumor-infiltrated tissue from non-tumorous brain tissue during neurosurgical tumor excision is a major challenge in neurosurgery. It is critical to achieve full tumor removal since it directly correlates with the survival rate of the patient. Optical coherence tomography (OCT) might be an additional imaging method in the field of neurosurgery that enables the classification of different levels of tumor infiltration and non-tumorous tissue. This work investigated two OCT systems with different imaging wavelengths (930 nm/1310 nm) and different resolutions (axial (air): 4.9 μm/16 μm, lateral: 5.2 μm/22 μm) in their ability to identify different levels of tumor infiltration based on freshly excised ex vivo brain samples. A convolutional neural network was used for the classification. For both systems, the neural network could achieve classification accuracies above 91% for discriminating between healthy white matter and highly tumor infiltrated white matter (tumor infiltration >60%) .This work shows that both OCT systems with different optical properties achieve similar results regarding the identification of different stages of brain tumor infiltration.